MINERAL RESOURCE POTENTIAL OF THE RUSSIAN FEDERATION: CONDITION AND INNOVATION USE TRENDS - O. V. Petrov (Экономика региона, 2010)
The paper deals with the issues concerned with market appraisal of mineral resource potential of the Russian Federation. Strategy regarding reproduction and innovation use of the mineral resource potential on an expanded scale has been substantiated. Mineral resource potential of the Russian Federation is considered by the author as a major factor of budgeting and national well-being. The structure of national wealth (in terms of minerals) has been analyzed. New Centers for economic development have been justified; they are an essential supplemental base to the existing large oil-and-gas and mining regions with considerably depleted potential. Th e statement related to the fact that Centers for economic development are to be planned with regard to innovation development of the mineral resource base, has been substantiated